Peran Efisiensi Biaya dan Ketepatan Waktu dalam Hubungan Harga Satuan Pekerjaan dan Kualitas Proyek Konstruksi - Iwan Setiawan; Zulkifli Lubis (Universitas Veteran Bangun Nusantara, 2026)
The discrepancy between the Government-established Unit Price of Work (HSP) and the contractor-formulated HSP is a phenomenon that can potentially impact construction project performance, particularly regarding cost efficiency, schedule adherence, and project quality. This study aims to analyze the influence of Government HSP and Contractor HSP on construction project quality, both directly and through the mediating roles of cost efficiency and schedule adherence. A quantitative approach utilizing Partial Least Squares Structural Equation Modeling (SEM-PLS) was employed. Data were gathered via a questionnaire survey involving 300 respondents—comprising Commitment-Making Officials (PPK), supervising consultants, and executing contractors—involved in construction projects in East Kalimantan Province. The SEM-PLS analysis reveals that Government HSP has a positive and significant effect on cost efficiency (path coefficient of 0.64), while Contractor HSP has a positive and significant effect on schedule adherence (path coefficient of 0.62). Both cost efficiency and schedule adherence significantly influence project quality. Mediation analysis indicates that cost efficiency and schedule adherence serve as significant mediators. The structural model demonstrates strong predictive relevance, with positive values across all endogenous variables. These findings underscore that establishing HSP values that are realistic and aligned with field conditions plays a strategic role in ensuring the quality of construction projects.